Simplified Reversed Chloroquines To Overcome Malaria Resistance to Quinoline-Based Drugs - Gunsaru, Bornface (Antimicrob Agents Chemother, 2017)
Building on our earlier work of attaching a chemosensitizer (reversal agent) to a known drug pharmacophore, we have now expanded the structure-activity relationship study to include simplified versions of the chemosensitizer. The change from two aromatic rings in this head group to a single ring does not appear to detrimentally affect the antimalarial activity of the compounds. Data from in vitro heme binding and β-hematin inhibition assays suggest that the single aromatic RCQ compounds retain activities against Plasmodium falciparum similar to those of CQ, although other mechanisms of action may be relevant to their activities.